2014
DOI: 10.1177/1941406414520703
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Iron Status of Adolescents From Selected Secondary Schools in Ogun State, Nigeria

Abstract: Purpose. We assessed the anthropometric and iron status of adolescents from selected secondary schools in Ogun State, Nigeria. Methods. In this cross-sectional study, anthropometric data, nutrient data, and blood samples were collected from 127 adolescents in Nigeria. Demographic information of the adolescents was obtained in the language of choice using validated questionnaires. Anthropometric indices (weight and height), multiple iron status indicator (hemoglobin, serum ferritin, and transferrin receptor) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Previous studies in Nigerian children and adolescents reported fat intakes ranging from 44.3 to 84.8 g/d [7,8,28], whereas we saw intakes at closer to 30 g/d. One possible explanation is that our sample included younger children, beginning at the age of 4 years, whereas the youngest children in the previous studies were 6 years old [7], 8 years old [28], and 10 years old [8]. However, even among older children, the fat intakes reported in our study tended to be lower than previous reports.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Previous studies in Nigerian children and adolescents reported fat intakes ranging from 44.3 to 84.8 g/d [7,8,28], whereas we saw intakes at closer to 30 g/d. One possible explanation is that our sample included younger children, beginning at the age of 4 years, whereas the youngest children in the previous studies were 6 years old [7], 8 years old [28], and 10 years old [8]. However, even among older children, the fat intakes reported in our study tended to be lower than previous reports.…”
Section: Discussioncontrasting
confidence: 86%
“…We compared protein intakes with the AMDR, whereas previous studies in Nigeria compared protein intakes to the RNI [ 7 , 8 ] or presented average protein intakes as a percentage of total energy [ 28 ]. Amounts of protein consumed by school-age children in Ibadan were similar to those reported in previous studies in Enugu State [ 7 ] and Ogun State [ 8 , 28 ]. We also observed a decrease in protein intakes in older school children compared to the younger ones, which is similar to findings from the study in Enugu State [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the higher prevalence of anaemia in the female is due to rise in iron requirements due to menstruation [ 44 , 95 ]. Anaemia among female adolescents has consequences on their growth and development, the cognitive ability, and hence affects academic performances and irregular menstrual cycle [ 96 ]. It also affects physical fitness and work productivity and may lead to reproductive complications [ 94 ].…”
Section: Discussionmentioning
confidence: 99%